Auditory Working Memory Span of Children with (Central) Auditory Processing Disorders and Normal Children Aged 8 to 10 Year - Abdollah Moossavi; Bahareh Khavarghazalani; Yoones Lotfi; Saeedeh Mehrkian; Zahra Hosseinidastgerdi (Shiraz University of Medical Sciences, 2015)
Background: The aim of the present study was to assess the auditory working memory span of children with (central) auditory processing disorders (C) APDaged 8 to 10 years and to compare the results with normal ones. Methods: Twenty five children with (Central) Auditory Processing Disorders (8-10 years) and 75 normal children (8-10 years) from both genders participated in this comparative study. Participants were chosen by convenient sampling method to assess their auditory working memory (WM) span. Forward digit span, backward digit span and non-word repetition tests were used to evaluate the WM span. Nonparametric statistics (Mann-Whitney U) were used for comparing group differences. Results: Forward digit and backward digit and non-word repetition tests showed significant differences in mean scores between those with (C) APD and normal children (P<0.001). Conclusion: The results suggest that (C) APD children have poorer performance in the WM span than the age matched controls.